Lupus. - Isenberg, David (Facts (Oxford, England), 2008)
Lupus is a disorder in which the body's immune system attacks itself, culminating in disease which can affect multiple organs, including the skin, joints, heart, lungs, kidneys, and central nervous system. Lupus currently affects about 30,000 patients in the UK, 500,000 in the United States and tens of thousands throughout Europe. Whilst there have been great advances in research into the genetic background of lupus and new interventions such as stem-cell transplants, there isstill a surprising lack of information available for patients, carers and their families. Written by the former Preside.